O processo de construção do ethos do jornal Diário Popular do Paraguai, a imagem de si e do outro no discurso, uma análise do Jopará nas páginas policiais - Santos, Luciano Marcos do (2019)
This study analyzes the process of construction of a popular ethos in Diario Popular, a paraguayan newspaper, linked to the projection of images: self-image and of the other, realizable discursively, by lexical choices, in jopará, in the news of police section. It advocates that the discourse, as a symbolic object that produces senses, as an interactive act, in which, a form of saying is elaborated, presupposes the constitution of an image of those involved in this act. By the strategic choice of words, in jopara, by context, by its legitimacy, as a media product, the enunciator, newspaper in focus, constructs an ethos (preliminary ethos and discourse ethos) popular, whose engagement in interlocution makes possible the interpretation of some image projections, a self-image, of the characters in the stories and also of the reader profile. The analyzes, that approach the process of formation of the previous ethos and of the contract of communication, are developed through the application of 50 questionnaires to the newspaper`s readers, trade workers from Ciudad del Este, a Paraguayan city that borders Foz do Iguaçu, Brazilian city. The study on the constitution of the ethos shown was based on a corpus made up of 61 sequential editions, which correspond to the months of March and April 2011, specifically from the sections: Sucesos y Locales, in Diario Popular. The construction of the arguments, related to documentary analysis, is supported by excerpts, contextualized, interspersed. For that, it demanded a concatenation, theoretical and methodological, interdisciplinary, supported on Speech Analysis; Pierre Bourdieu`s Sociology of the Fields precepts; on Perelman, Tyteka`s Rhetoric (2002); on Patrick Charaudeuau`s Semiolinguistic of Discourse Analysis (2008) - appointment and Communication Contract; and on Maingueneau´s (2005) and Amossy`s (2005) models of understanding ethos. This work is justified, mainly, by the importance of studies dedicated to the use of words in public discourses, especially for embracing the jopara, as well as for understanding the process of persuasion connected to the construction of the self-image.